Evaluasi Nevirapine pada Terapi ARV Tahun Pertama dan Kedua Terhadap Fungsi Hati di Puskesmas Kecamatan Cilandak: Studi Kadar SGOT dan SGPT - Burhannudin, Burhannudin (Jurnal Fisioterapi dan Kesehatan Indonesia, 2023)
Anti-Retroviral Therapy (ART) is still the best medication for preventing and defeating the Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (HIV/AIDS) infection. However, the overall treatment needs a perpetual process and monitoring for effect. Nevirapine, one of the ART regimens, was recommended for use due to its high efficacy, even though it was suspected of causing liver hepatotoxicity. Liver disorders can be diagnosed by examining SGOT and SGPT blood levels in HIV/AIDS patients. The study aimed to monitor the effect of using Nevirapine on SGOT and SGPT blood levels in the first and second years of administration. This observational study with a cross-sectional design of Nevirapine users in Puskesmas Cilandak was from January 2019 to December 2022. The subject of the study was 113 respondents in total, with 40 respondents administered for one year of Nevirapine and 73 administered for two years. The one-year administration of Nevirapine showed that the abnormal SGOT and SGPT blood level in HIV/AIDS patients was equal to their baseline measurement (2.50%). On the other hand, the two years administration showed an increasing number of SGOT (30.20%) and SGPT (60.28%) in the blood. Spearman’s rank test was tested to check the correlation between the increasing level of SGOT and SGPT during the therapy, showing that SGOT and SGPT increased from one year to two years of the administration of Nevirapine with 0.33 (p<0.05) and 0.56 (p<0.05), respectively. The increasing SGOT and SGPT blood levels indicated a liver disorder. Yet another profound approach to examination needs to be done furthermore. Nevirapine administration to HIV/AIDS patients must be monitored perpetually to prevent further liver damage.